KONSEP DAN TANTANGAN PENGGUNAAN TEKNOLOGI E-MONEY SEBAGAI ALAT PEMBAYARAN ALTERNATIF DI INDONESIA - Lalu Delsi Samsumar (Universitas Methodist Indonesia, 2016)
The use of electronic money (e-money) in the next few years in Indonesia will grow significantly. With e-money, will facilitate public transactions without the need to use cash. E-money is a non-cash payment instruments, these products save some money value stored in the electronic equipment. Nominal money stored electronically done by exchanging a sum of money or by debiting a bank account which is then stored in electronic equipment. Implementation of e-money in Indonesia, including late if compared to countries such as Hong Kong and Singapore. E-money introduced since 2007, while in Hong Kong in 1997 and Singapore in 2000. With the condition of the infrastructure in Indonesia, it takes a long time to peopleaccustomed to using e-money. Cultural society accustomed to transact in cash will be a challenge. To increase public confidence, Bank Indonesia has issued a regulation with e-money transactions. The use of e-money will also facilitate the public, because no longer need to carry cash. Transact using e-money is safe, because it uses technology that attention to standardization such as the use of chips.